Managing Investment Programs оf Electric Power Companies - K. E. Vedenyev (Вестник Российского экономического университета имени Г. В. Плеханова)
In the situation of digitalization of finance and economic processes to create and increase values and investment appeal corporations are obliged to acquire new sources of capital stock, to build up accumulations and keep them on the optimal level. Investment programs of electric power companies are personified know-how with simultaneous administrative control over prices for products put out by them. Each company continuously looks for sources of long-term investment by developing investment strategies appealing for investors, for the development of own business and tries to earn finance, social capital and reputation. Electric power companies usually have a big share of state ownership, which is controlled with difficulties, especially when horizontal transfers of this ownership go on. The goal of the article is to substantiate the model of technological price control of investment processes at electric power companies, which stipulates evaluation of capital structure and accumulation processes and investment practice of efficiency support, first of all for protection of their interests. For companies investment is a key driver of development, it gives an opportunity to extend business, enter new markets, modernize production and equipment and change ideology of personnel, therefore, companies always do their best to attract investors. The target model of exercising technological and price control of the investment program at electric power companies demonstrates the necessary conditions of balancing dynamic pricing for company products, its securities and management strategy with capital value and keeping it on the optimum level when evaluating investment project efficiency. In world practice there is a sufficient number of methods and algorithms to control investment programs and business, however finance environment, methods and criteria of evaluation evolve and tools of audit and analysis change.